Stratopause region parameters for Davis - KLEKOCIUK, ANDREW (hasPrincipalInvestigator); KLEKOCIUK, ANDREW (processor); Australian Antarctic Data Centre (publisher)
This indicator is no longer maintained, and is considered OBSOLETE. INDICATOR DEFINITION Lidar observations at Davis Station, Antarctica, are used to obtain monthly average values of the temperature at the stratopause, the altitude of the stratopause, and the temperature and altitude of the 0.5hPa pressure level. TYPE OF INDICATOR There are three types of indicators used in this report: 1.Describes the CONDITION of important elements of a system; 2.Show the extent of the major PRESSURES exerted on a system; 3.Determine RESPONSES to either condition or changes in the condition of a system. This indicator is one of: CONDITION RATIONALE FOR INDICATOR SELECTION A general cooling of the stratosphere is predicted to accompany anthropogenically enhanced greenhouse-gas warming of the lower atmosphere. This should lead to changes in the altitude and temperature of the stratopause region, and a decrease in the height of standard pressure surfaces in the stratosphere and mesosphere. However, perturbations to the thermodynamics of the stratopause region may be caused by inter-annual variability in the lower atmosphere, volcanic events, and solar-cycle changes. Long-term quantification of stratopause region parameters will aid in understanding and predicting natural and anthropogenic variability. The 0.5hPa pressure altitude has been chosen as this lies near the stratopause at Davis, and temperatures for this pressure level are routinely obtained by satellite remote sensing instruments. DESIGN AND STRATEGY FOR INDICATOR MONITORING PROGRAM Spatial scale: Davis Station, Antarctica Temporal scale: Monthly Measurement technique: Lidar (532nm wavelength) RESEARCH ISSUES Changes in the thermodynamics of the stratoapuse region has implications for the atmosphere at lower altitudes. To obtain a more comprehensive picture of the spatial extent of these changes, the underlying physics, and future implications, the Davis observations should be assimilated into research incorporating a diverse body of observations and model predictions. Important additional data will come the remote sensing of temperatures and winds in the mesopause region, from instruments at Davis including the MF radar and the proposed VHF radar, and other Antarctic measurements.